Exploring social impairment in those with opioid use disorder: linking impulsivity, childhood trauma, and the prefrontal cortex - Thais Costa Macedo de Arruda; Laura Sinko; Paul Regier; Altona Tufanoglu; Adrian Curtin; Anne M. Teitelman; Hasan Ayaz; Peter F. Cronholm; Anna Rose Childress (BMC Psychiatry)
Abstract Background Challenges with social functioning, which is a hallmark of opioid use disorder (OUD), are a drawback in treatment adherence and maintenance. Yet, little research has explored the underlying mechanisms of this impairment. Impulsivity and corresponding neural alterations may be at the center of this issue. Childhood adversity, which has been linked to both impulsivity and poorer treatment outcomes, could also affect this relationship. This study explores the relationship between impulsivity, social functioning, and their neural correlates in the prefrontal cortex, while examining the potential moderating effects of childhood trauma in individuals recovering from OUD. Methods Participants with (N = 16) and without (N = 19) social impairment completed a survey (e.g., social functioning, Barrat’s Impulsivity Scale, Adverse Childhood Experiences (ACEs) and cognitive tasks while undergoing neuroimaging. Functional near infrared spectroscopy (fNIRS), a modern, portable, wearable and low-cost neuroimaging technology, was used to measure prefrontal cortex activity during a behavioral inhibition task (Go/No-Go task). Results Those who social functioning survey scores indicated social impairment (n = 16) scored significantly higher on impulsivity scale (t [33]= -3.4, p < 0.01) and reported more depressive symptoms (t [33] = -2.8, p < 0.01) than those reporting no social impairment (n = 19). Social functioning was negatively correlated with impulsivity (r=-0.7, p < 0.001), such that increased impulsivity corresponded to decreased social functioning. Childhood trauma emerged as a moderator of this relationship, but only when controlling for the effects of depression, B=-0.11, p = 0.023. Although both groups had comparable Go/No-Go task performance, the socially impaired group displayed greater activation in the dorsolateral (F(1,100.8) = 7.89, p < 0.01), ventrolateral (F(1,88.8) = 7.33, p < 0.01), and ventromedial (F(1,95.6) = 7.56, p < 0.01) prefrontal cortex duringthe behavioral inhibition task. Conclusion In addition to being more impulsive, individuals with social impairment exhibited greater activation in the prefrontal cortex during the Go/No-Go task. Furthermore, the impact of impulsivity on social functioning varies depending on ACEs, such that higher levels of ACEs corresponded to a stronger negative relationship between impulsivity and social functioning, highlighting its importance in treatment approaches. These findings have implications for addressing social needs and impulsivity of those in recovery, highlighting the importance of a more personalized, integrative, and trauma-informed approach to intervention.